Hospital managers' views on the state of patient safety culture across three regions in Ghana - Immaculate Sabelile Tenza; Priscilla Y. A. Attafuah; Patience Abor; Edward Nketiah-Amponsah; Aaron Asibi Abuosi (BMC, 2022)
Abstract Background Improving patient safety culture in healthcare organisations contributes positively to the quality of care and patients' attitudes toward care. While hospital managers undoubtedly play critical roles in creating a patient safety culture, in Ghana, qualitative studies focussing on hospital managers' views on the state of patient safety culture in their hospitals remain scanty. Objective This study aimed to explore the views of hospital managers regarding compliance to patient safety culture dimensions in the selected hospitals in the Bono, Greater Accra, and Upper East regions of Ghana. Methodology This was a qualitative exploratory study. A purposive sampling of all hospital managers involved in patient safety practices was conducted. The sampled managers were then invited to a focus group discussion. Twelve focus group discussions with each consisting of a maximum of twelve participants were conducted. The ten patient safety culture dimensions adapted from the Agency for Healthcare Research and Quality's patient safety culture composite measures framed the interview guide. Deductive thematic content analysis was done. Lincoln and Guba's methods of trustworthiness were applied to ensure that the findings are valid and reliable. Findings Positive patient safety culture behaviours such as open communication, organisational learning, and strong teamwork within units, were an established practice in the selected facilities across Ghana. Lack of teamwork across units, fear of reporting adverse events, the existence of a blame culture, inconsistent response to errors, extreme shortage of staff, sub-standard handover, lack of management support with resources constrained the patient safety culture. The lack of standardised policies on reporting adverse events and response to errors encouraged managers to use various approaches, some resulting in a blame culture. Staff shortage contributed to poor quality of safety practices including poor handover which was also influenced by lateness to duty. Conclusion Prompt and appropriate responses by managers to medical errors require improvements in staffing and material resources as well as the enactment of standard policies across health facilities in the country. By so doing, hospital managers would contribute significantly to patient safety, and help build a patient safety culture in the selected hospitals.